Structural and Dielectric Behaviour of Blend Polymer Electrolyte based on PEO-PAN + LiPF6 - Arya, Anil; Sharma, Sweety; Sharma, A. L.; Kumar, Dinesh; Sadiq, Mohd (Asian Journal of Engineering and Applied Technology, 2016)
Solid polymer electrolytes (SPEs) have recently gained more research interest in the area of materials science due to their wide application range in energy storage/conversion devices like batteries, supercapacitors, solar cells and sensors. A blend polymer electrolyte based on polyethyeleneoxide (PEO) and polyacrylonitrile (PAN) doped with Lithium Hexaflurophosphate (LiPF6) has been prepared by solution casting technique using Dimethyalformamide (DMF) as a solvent. The complex formation has been studied using X-ray diffraction (XRD). The decrease in intensity and broadness in peak revels the amorphous phase formation. The dielectric study of PS films has been done which gives the two order decrement in relaxation time (i.e. 10-4 – 10-6) which is directly related to faster on dynamics in polymer electrolytes. The analysis has shown the dielectric polarization at low frequencies. The dielectric peak has been observed to shift toward the higher frequency side with the addition of salt, suggesting the low sample viscosity and faster conduction of ions.